Imaging neurodegeneration markers are associated with multiple pathophysiological mechanisms in the early stages of the Alzheimer's continuum. (December 2021) - Salvadó, Gemma; Shekari, Mahnaz; Milà‐Alomà, Marta; Sánchez‐Benavides, Gonzalo; Operto, Greg; Falcon, Carles; Cacciaglia, Raffaele; Niñerola‐Baizán, Aida; Perissinotti, Andrés; Minguillón, Carolina; Fauria, Karine; Kollmorgen, Gwendlyn; et al.
Abstract: Background: Multiple pathophysiological pathways are altered in the early stages of Alzheimer's disease (AD). The associations between these pathways and structural and metabolic brain changes are not clear. This study investigated associations between imaging neurodegeneration markers and cerebrospinal fluid (CSF) markers of amyloid‐β ([Aβ]; Aβ42/40 ) and tau pathology (p‐tau), neurodegeneration (t‐tau and NfL), synaptic (neurogranin), glial activity (GFAP, YKL‐40, sTREM2, s100b and IL‐6) and α‐synuclein, in cognitively unimpaired individuals. Method: Cognitively unimpaired participants (N=291) from the ALFA+ cohort, with data available for T1‐weighted MRI, FDG‐PET, CSF biomarkers and cognitive measures, were included (Table 1). CSF biomarkers were measured using the exploratory Roche NeuroToolKit assays, a panel of automated robust prototype immunoassays (Roche Diagnostics International Ltd). A combination of weighted measures of all CSF biomarkers (components) were derived to explain the maximal variance of imaging neurodegeneration markers (gray matter [GM] volume and FDG‐uptake) using the Projection to Latent Spaces method. This method allowed to assess multivariate associations between CSF and neuroimaging biomarkers avoiding colinearity problems. Associations between these components with AD risk factors, A/T stages and AD‐related measures were investigated. Result: GM volume and FDG‐uptake were greater with higher levels of CSF tau and glial markers (Fig. 1A). Glial markers and neurogranin showed both positive and negative associations with imaging neurodegeneration markers in different areas (Fig. 1B−C). With increased CSF Aβ levels, α‐synuclein was negatively associated with GM volume (Fig. 1D). Aβ pathology was associated with hippocampal‐hypometabolism (Fig. 1E). These components also showed significant associations with age, sex and APOE‐ε4 carriership (Fig. 2) and with A/T stages (Fig. 3).Only the tau‐glial and the standalone glial components were associated with AD‐signature measures (Fig. 3). The tau‐glial component showed a trend to lower cognition (Fig. 3). Conclusion: In early AD, increases in CSF levels of tau and glial markers were associated with increased GM volume and metabolism, and showed a trend to a decrease in cognitive function. Glial, synaptic dysfunction, α‐synuclein and Aβ markers were also related to changes in volume and metabolism. These results suggest a complex association between multiple pathophysiological pathways and imaging neurodegeneration markers in the early Alzheimer's continuum . Determining these relationships is crucial to modelling prevention trials targeting these pathways.